Comprehensive Review of Public Health Policies, Disease Prevention, and Community Health Outcomes - Alyami, Abdullah Mohammed Mana; Al shahi, Mohammed Salem Hamad; AL shahe, Mohammad Mana; alshahi, Hamad Salem; AL shahe, Mohammad Saleh Ali; ALshahe, Saleh Mohammad Mani; AL shahi, Ibrahim Salem; Al- yami, Mohammed Rashed Mane Al- monajim; Al-munajim, Mana Rashed Mana; Al Alshahi, Ali Nasser Mahdi (Journal of Ecohumanism, 2024)
Government measures have prominent impacts on the population's health and the disease epidemiology in the territory. This review, therefore, examines policy measures and their efficiency in tackling diseases and the consequent positive health impacts. This paper concentrates on the outcomes of tobacco control and accomplishments of NSPs and vaccination and community-based programs; it measures these accomplishments and proposes future research. The present review builds on such an approach by compiling evidence from the case studies and public health data that stress the significance of evidence-based policymaking, the application of health policies for everyone, and the continuous involvement of the public.